Digestible methionine levels for white-egg layer pullets from 7 to 12 weeks of age - Jalceyr Pessoa Figueiredo Júnior; Fernando Guilherme Perazzo Costa; Ricardo Romão Guerra; Marcelo Helder Medeiros Santana; Matheus Ramalho de Lima; Sarah Gomes Pinheiro (Acta Scientiarum. Animal Sciences, 2020)
An experiment was carried out to evaluate the requirement of digestible methionine for growing pullets at growth phase (7 to 12 weeks of age). A completely randomized design was distributed in five treatments, six replicates, and 15 pullets per experimental unit. 450 Dekalb White pullets from the 7th weeks of age, with an average initial weight of 313.14 ± 12.49 g were used. Dietary treatments consisted in five diets supplemented with DL-Methionine which resulted in five levels of digestible methionine (0.266, 0.294, 0.322, 0.350, and 0.378 %). Performance, serological blood, histopathology and histomorphometry data were evaluated. Quadratic responses were observed for final live weight (p < 0.0143), weight gain (p < 0.0073), feed conversion ratio (p < 0.0058), glycogen deposition in the liver (p < 0.0001), gamma-glutamyl transferase enzyme activity (p < 0.0008), and villus height (p < 0.0024) with digestible dMet levels. In conclusion, the use of 0.343 % dMet, corresponding to a dMet:dLys ratio 55, is recommended for white-egg pullets from 7 to 12 weeks of age.